The Bogleheads' guide to investing - Lindauer, Mel, 1938-; Larimore, Taylor, 1924-; LeBoeuf, Michael (Wiley, 2022)
"The followers of John C. Bogle have made simple communication about investing an art form. During its more than 20 years of existence, the Bogleheads have moved from a loose association of dedicated investors to a formal website, Bogleheads.org. (The Bogleheads previously gathered online at the "Vanguard Diehards" message board on Morningstar.com.) The Bogleheads website now attracts an incredible 1.5 million visits per month and as many as 1,500 individual posts each day"--